2002
DOI: 10.1161/01.cir.0000018443.44005.d8
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Tone Variations Before the Onset of Paroxysmal Atrial Fibrillation

Abstract: Background-Mechanisms favoring the occurrence of paroxysmal atrial fibrillation (PAF) are complex and poorly defined. This study was designed to analyze dynamic changes in autonomic tone preceding the onset of PAF in a large group of patients. Methods and Results-Holter tapes from 77 unselected consecutive patients (63 men and 14 women aged 58Ϯ12 years) with PAF were analyzed. A total of 147 episodes of sustained AF (Ͼ30 minutes) were recorded and submitted to time-domain and frequency-domain heart rate variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
294
0
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(311 citation statements)
references
References 30 publications
(31 reference statements)
13
294
0
4
Order By: Relevance
“…103,105,114,116,124,355,576,577,578,579,580,581,582 Because the GP are consistently located within areas of highly fractionated atrial potentials (FAPs), also referred to as CFAEs, 103,105,114,116,124,355,576,577,578,579,580,581,582,583,584 it is useful to begin with a fractionation map of the LA and PVs during AF. The LA FAPs are usually located in four areas: (1) LAA ridge FAP area (between LAA and left PVs); (2) superior left FAP area; (3) inferoposterior FAP area; and (4) anterior right FAP area (Figure 4).…”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
“…103,105,114,116,124,355,576,577,578,579,580,581,582 Because the GP are consistently located within areas of highly fractionated atrial potentials (FAPs), also referred to as CFAEs, 103,105,114,116,124,355,576,577,578,579,580,581,582,583,584 it is useful to begin with a fractionation map of the LA and PVs during AF. The LA FAPs are usually located in four areas: (1) LAA ridge FAP area (between LAA and left PVs); (2) superior left FAP area; (3) inferoposterior FAP area; and (4) anterior right FAP area (Figure 4).…”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
“…24) Bettoni, et al suggested that changes in autonomic nervous activities were associated with the occurrence of atrial fibrillation. 25) On the other hand, Pitzalis, et al 7) and Coumel 8) reported tachycardiainduced VPC and pointed out the possibility of involvement of sympathetic activities. Moreover, Fleg, et al and Pfeifer, et al described an age-related increase in plasma norepinephrine in elderly subjects at maximum exercise and in the supine position, respectively.…”
Section: ∆Thbmentioning
confidence: 99%
“…76,77 Both sympathetic and parasympathetic stimuli may be involved, 76 although in humans, the extent and importance of autonomic influences vary based on patient characteristics and comorbidities. 78 Ganglionated plexi (GP) are epicardial networks of autonomic nervous tissue present near the junctions between the pulmonary veins and LA.…”
Section: The Influence Of the Autonomic Nervous System And Ganglionatmentioning
confidence: 99%